Framework of distributed controlling via smartphone for industrial automation application - Phua, Ging Sheng (2014)
Programming language that is used in industrial is platform specific, when hardware is updated or replaced by a newer hardware, the entire binary software needed to be changed and modified. Software that has been written is not able to run on different hardware platform without recompiling the source code. Besides that, the same code that is executed on machine is not able to be executed on computer for any hardware simulation or testing. Machine running code is not compatible with computer running code, thus, different types of source code are needed for computer simulation and real time platform respectively. This research was focused on extending Smartphone and Java platform into automation environment where users are able to monitor and control the targeted system regardless of any location by utilizing internet. The main task of this research had been working on creating new framework of distributed controlling and computing via smartphone. Platform independent frameworks of classes that implement internet protocol were designed to provide interaction over client server paradigm and finally all frameworks were then integrated over a system which allows access to automation control manipulate and monitor via smartphone over wireless internet network protocol. Through this approach, Smartphone and Java platform's extendibility and adaption in different environment with Java features inherited were proven successfully. As a result, Industrial automation can use Java to produce systems that perform more reliably, improve programmer productivity, time efficiency and even provide binary compatibility across hardware platforms. Using Java, when comes to hardware simulation, the same application class files that run on the target machine can also execute on a desktop computer for development and debugging due to its platform independent ability. It simplifies remote monitoring and controlling in several ways where its internet working based language allows it to run on any web browser or any other networking platform. In the event of a hardware fault, a developer could also write a dynamic Java classes that monitor a set of sensors on the hardware for maintenance and troubleshooting. Not only can dynamic troubleshoot the behavior of the hardware, but it can also be used to patch existing code or add additional functions without stoppage or modification of machine. The ability to change a single source file, recompile it and then dynamically download only the changed class file and link it with a running JVM provides added flexibility for software maintenance. Hardware independence ability allows developers to simulate the run-time environment on a desktop computer, greatly reducing development time and debugging is required only on a single version of source code, once for all platforms. This reduces the project overhead and maintenance by greatly simplifying project build configurations, reducing coding errors and simplifying bug tracking and change requests.